CHANGES IN THE MORPHOLOGICAL PARAMETERS OF THE STOMACH MUCOSA IN WHITE MALE RATS DURING POLYPHARMASY - Toshmamatov Bakhtiyor Norbekovich; Djumanova Nargiza Eshmamatovna (Web of Journals Publishing, 2024)
Anti-inflammatory drugs are one of the main tools for the treatment of acute and chronic pain in a wide range of diseases and pathological conditions. The use of anti-inflammatory drugs is an integral part of the practice of therapists, rheumatologists, neurologists, anesthesiologists, surgeons, traumatologists, gynecologists, etc.
Keywords: stomach, stomach wall, mucous membrane, polypharmacy, lymph, tissue.